2022
DOI: 10.3390/en15103711
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Physical, Mechanical and Energetic Characteristics of Pine Sawdust by the Addition of up to 40% Agave durangensis Gentry Pellets

Abstract: Agave durangensis Gentry biomass, as a residue from the mezcal production process, may be an interesting bioenergy alternative; however, its high ash content limits its application. In this study, pellets were generated with agave fiber mixed with Pinus species sawdust in the following six proportions (%): 100–0 (control), 80–20, 60–40, 40–60, 20–80 and 0–100 (control). The physical, chemical and energetic properties of the pellets were evaluated according to the UNE-EN ISO 17225-6, UNE EN ISO 17827-2, UNE-EN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Experimental results demonstrated that torrefaction and densification technologies were effective methods to obtain higher quality torrefied pellets compared to regular wood pellets [125,126]. The pelletization process was also used to revalorize the wastes from the mezcal industry [31], by using mixtures of Agave durangensis fiber and pine sawdust. The proportion of 80% of A. durangensis fiber: 20% pine sawdust registered: volatile material 86.2%, ash 6.5%, fixed carbon 7.3%, calorific value 14.1 MJ/kg, and bulk density of 726.0 kg/m 3 .…”
Section: Pelletsmentioning
confidence: 99%
“…Experimental results demonstrated that torrefaction and densification technologies were effective methods to obtain higher quality torrefied pellets compared to regular wood pellets [125,126]. The pelletization process was also used to revalorize the wastes from the mezcal industry [31], by using mixtures of Agave durangensis fiber and pine sawdust. The proportion of 80% of A. durangensis fiber: 20% pine sawdust registered: volatile material 86.2%, ash 6.5%, fixed carbon 7.3%, calorific value 14.1 MJ/kg, and bulk density of 726.0 kg/m 3 .…”
Section: Pelletsmentioning
confidence: 99%
“…Recientemente se han desarrollado numerosos estudios sobre la diversidad y estructura en masas forestales de coníferas y latifoliadas de interés comercial para un aprovechamiento sustentable como los generados por (López-Hernández et al, 2017;Monárrez-González et al, 2018;Ramírez-Santiago et al, 2019;Blancarte-Contreras et al, 2022;Chávez-Aguilar et al, 2022;Muñoz-Flores et al, 2022).…”
Section: Introductionunclassified
“…Atabani et al [52] produced and burned pellets made from spent coffee grounds and other waste biomass. Blancarte-Contreras [53] investigated the mechanical and energetic properties of pellets produced from agave fiber mixed with Pinus species sawdust in six different proportions. Chojnacki et al [54] added wastes from the production of apple, carrot, and red beet juice to barley straw and examined their influence on the density, hardness, ash content, and calorific value of pellets.…”
Section: Introductionmentioning
confidence: 99%